2023
DOI: 10.1002/csc2.20992
|View full text |Cite
|
Sign up to set email alerts
|

A bermudagrass variant exhibits strong tolerance to low temperature associated with enhanced sugar metabolism and cold‐responsive pathways

Abstract: As a warm‐season turfgrass, bermudagrass (Cynodon) is sensitive to low ambient temperature. The objectives of this study were to evaluate cold tolerance of a new variant Chuannong‐3 under field condition and to further elucidate metabolic and molecular bases of cold tolerance in the Chuannong‐3 as compared to triploid Tifdwarf (Cynodon transvaalensis × Cynodon dactylon) and tetraploid common bermudagrass 001 (C. dactylon). The Chuannong‐3 was identified as a triploid bermudagrass based on ploidy analysis. Chua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In this process, ZmHSBP2 acted as an antagonist of ZmHSF2 [ 56 ]. Our previous study has also shown that the enhanced cold tolerance of Chuannong-3 was related to the improvement in raffinose biosynthesis for osmotic adjustment and osmoprotection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, ZmHSBP2 acted as an antagonist of ZmHSF2 [ 56 ]. Our previous study has also shown that the enhanced cold tolerance of Chuannong-3 was related to the improvement in raffinose biosynthesis for osmotic adjustment and osmoprotection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data were recorded and organized using Excel 2019 (Microsoft Office 2019, Albuquerque, NM, USA). Differences among treatment means were tested using Fisher’s protected least significance (LSD) test at a 0.05 probability level [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation